1996
DOI: 10.1111/j.1365-2044.1996.tb15064.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glycopyrrolate on postoperative pain and analgesic requirements following laparoscopic sterilisation

Abstract: SummaryIn order to evaluate the contribution of tuba1 spasm to pelvic pain following laparoscopic sterilisation, we have studied the effecr ofglycopyrrolate, an anticholinergic agent with antispasmodic properties, on 60 ASA 1 and 2 patients presenting as day-cases ,for laparoscopic sterilisation using Filshie clips. In a randomised, double-blind, controlled trial, patients received either glycopyrrolate 0.3 mg or saline intravenously prior to induction of anaesthesia. Compared with the control group, patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 14 publications
1
20
0
1
Order By: Relevance
“…Subphrenic/ shoulder pain is the first type of pain, and may persist until the third to fourth postoperative day (Alexander, 1997;Dobbs et al, 1987;Goldstein et al, 2000;Guard & Wiltshire, 1996). None of the patients in this study reported this type of pain.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Subphrenic/ shoulder pain is the first type of pain, and may persist until the third to fourth postoperative day (Alexander, 1997;Dobbs et al, 1987;Goldstein et al, 2000;Guard & Wiltshire, 1996). None of the patients in this study reported this type of pain.…”
Section: Discussionmentioning
confidence: 53%
“…Spasmodic/cramping pain is the third type of pain, and hardly ever lasts longer than three to four hours (Dobbs et al, 1987;Edwards et al, 1991;Guard & Wiltshire, 1996). The take-home questionnaire revealed that eight subjects (six hours after surgery), four subjects (24 hours), and five subjects (48 hours) reported abdominal pain.…”
Section: Discussionmentioning
confidence: 99%
“…Pain following laparoscopic sterilization has this characteristic, so an anti-spasmodic agent would be ideal for its treatment. Glycopyrrolate an anticholinergic drug was efficient to decrease PO pain when administered before surgery in patients submitted to tubes occlusion by Filshie 15 clamp technique 20 . The N-butylscopolamine, a muscarinic cholinergic antagonist, is widely used to treat colic pain with the advantage of fast onset when intravenously administered.…”
Section: Discussionmentioning
confidence: 99%
“…A dor que segue a laqueadura laparoscópica tem esta característica, por isso um agente anti-espasmódico seria a opção ideal para o seu tratamento. O glicopirroplato, agente anticolinérgico, mostrou-se eficaz em reduzir a dor PO, quando administrado antes da cirurgia de pacientes que ligaram as tubas uterinas com clipes de Filshie 20 . A N-butilescopolamina, antagonista colinérgico muscaríni-co, é muito utilizada no tratamento da dor em cólicas e tem como vantagem o rápido início de ação quando administrada pela via venosa.…”
Section: Discussionunclassified
“…The degree of pain reported among this post-surgical population can range from menstrual cramping to being severe enough to justify an unplanned hospital admission (Cade & Kakulas, 1995). Researchers who have previously examined pharmacological interventions of providing the most effective pain relief for postoperative ILBTS patients have been unable to conclude which modality is the most efficacious (Guard & Wiltshire, 1996;Hunter & Fogarty, 1996;Kelly, Baker, Robertson, & Noble, 1994;Van EE, Hemrika, De Blok, Van Der Linden, & Lip, 1996). Therefore, the existing variability in post-laparoscopic pain warranted further examination and provided a foundation for our study.…”
mentioning
confidence: 99%